Gender Inequality and Elite Working Women in Kirima Sub-County Kanungu District. - Namanya, Precious (Kabale University, 2023)
The General objective of the study was to examine Gender Inequality and Welfare of rural elite working women of Kirima Sub-county Kanungu District. The study was guided by the following Specific Objectives of the Study, to find out the factors that influence gender inequality among rural elite working women, to ascertain the challenges faced by rural elite working women, and to explore mechanisms to reduce gender inequality among rural elite working women in Kirima Sub-county Kanungu District. The study adopted a descriptive research design. Both quantitative and qualitative data were collected and this enabled the researcher to draw valid and dependable conclusions and recommendations of the study. Using Krejicie and Morgan's table of determination of sample size from a given study population (1970), the Study population was put into strata namely 56 elite rural working women and 10 local leaders. The study engaged a total of sixty-six (66) respondents. Data collection methods used to collect data included interviews and questionnaires. The data was then organized, entered into the computer, and analyzed using Microsoft Excel. The study results were later presented in the form of tables for easy interpretation. The findings revealed that gender inequality among rural working women within employment is the division of jobs. In Kirima sub-county, there is an inherent belief that men are simply better equipped to handle certain jobs as most of the time, those are the jobs that pay the best. The findings revealed that pay inequity is one of the most major issues that women employees have to face at their workplace as most of the time despite being more proficient and qualified than fellow male employees, women workers are paid less than males for the same amount. The findings from the study also revealed that Pay (and Demand) the Same Salary for equal Work should be promoted. Based on the conclusions, the researcher noted that there is a need to have proper value to women's work which should be emphasized. The unpaid work women and girls do provide the foundation for the global economy. This fact needs to be highlighted more in the media, with the private sector, and in communities.